Psychoanalysis as an ethical process - Drozek, Robert P. 1979- (Relational perspectives, 2019)
What role does ethics play in the practice of psychoanalysis and psychotherapy? For most of its history, psychoanalysis has viewed ethics as a "side issue" in clinical work--occasionally relevant, but not central to therapeutic action. In Psychoanalysis as an Ethical Process, Robert Drozek highlights the foundational importance of ethical experience in the therapeutic relationship, as well as the role that ethical commitments have played in inspiring what has been called the "relational turn" in psychoanalysis. Using vivid clinical examples from the treatment of patients with severe personality disorders, Drozek sketches out an ethically grounded vision of analytic process, wherein analyst and patient are engaged in the co-construction of an intersubjective space that is progressively more consistent with their intrinsic worth as human beings. Psychoanalysis can thus be seen as a unique vehicle for therapeutic and ethical change, leading to a dramatic expansion of agency, altruism, and self-esteem for both participants. By bringing our analytic theories into closer contact with our ethical experiences as human beings, we can connect more fully with the fundamental humanity that unites us with our patients, and that serves as the basis for deep and lasting therapeutic change. This book will be of interest to psychotherapists and psychoanalysts, as well as scholars in ethical theory and philosophy